The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ange.201807664
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Stereospecific C−H Coupling of Benzamides with Epoxides

Abstract: A Ni(OAc)2‐catalyzed C−H coupling of 8‐aminoquinoline‐derived benzamides with epoxides has been developed. The reaction proceeds with concomitant removal of the 8‐aminoquinoline auxiliary to form the corresponding 3,4‐dihydroisocoumarins directly. Additionally, the nickel catalysis is stereospecific, and the cis‐ and trans‐epoxides are converted into the corresponding cis‐ and trans‐dihydroisocoumarins with retention of configuration, which is complementary to previously reported palladium catalysis. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The important advantages of such annulation or cyclization reactions is that they can be used in the one-step synthesis of heterocycles that proceed via directed C−H bond activation. As of this writing, a variety of compounds, such as alkynes, 289−305 arynes, 306,307 allenes, 308−312 alkenes, 302,313−317 isonitriles, 318−323 nitriles, 324 nitroalkanes, 325 α-bromoketones, 326 epoxides, 327 carboxylates, 328 acids, or anhydrides 329 have been used as coupling partners in annulation or cyclization reactions of aromatic or aliphatic amides. In addition, a few studies have reported that the cyclization proceeds in an intramolecular manner, leading to the formation of a C−heteroatom bond.…”
Section: Nn-bidentate Directing Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important advantages of such annulation or cyclization reactions is that they can be used in the one-step synthesis of heterocycles that proceed via directed C−H bond activation. As of this writing, a variety of compounds, such as alkynes, 289−305 arynes, 306,307 allenes, 308−312 alkenes, 302,313−317 isonitriles, 318−323 nitriles, 324 nitroalkanes, 325 α-bromoketones, 326 epoxides, 327 carboxylates, 328 acids, or anhydrides 329 have been used as coupling partners in annulation or cyclization reactions of aromatic or aliphatic amides. In addition, a few studies have reported that the cyclization proceeds in an intramolecular manner, leading to the formation of a C−heteroatom bond.…”
Section: Nn-bidentate Directing Groupsmentioning
confidence: 99%
“…325 On the other hand, the use of higher nitroalkanes 326 Hirano and Miura reported the Ni-catalyzed stereospecific synthesis of 3,4-dihydroisocoumarins through the C−H coupling of aromatic amides with epoxides followed by cyclization (Scheme 62d). 327 In 2018, the Ni-catalyzed oxidative decarboxylative annulation of aromatic amides with orthofluoro-substituted (hetero)aromatic carboxylates was developed for the synthesis of phenanthridinone derivatives (Scheme 62e). 328 The reaction involves a sequence of events, including a C−H decarboxylative arylation at the orthoposition of aromatic amides followed by an intramolecular S N Ar reaction in the presence of Na 2 CO 3 at higher temperature, i.e., 130 °C.…”
mentioning
confidence: 99%